Search for exotic mono-jet events : in proton-proton collisions at √s = 7 TeV and 8 TeV with the ATLAS Detector /: in proton-proton collisions at √s = 7 TeV and 8 TeV with the ATLAS Detector. ([2016]) - Rossetti, Valerio
No abstract available